PROJECTA: An Art-Based Tool in Trauma Treatment - Fernández-Cao, Marián López; Camilli-Trujillo, Celia; Fernández-Escudero, Laura (Frontiers in Psychology, 2020)
Artistic images, of a universal nature and validated by global culture, are carriers of an emotional potential that can be used for therapeutic purposes in cultural centers as well as in clinical spaces. Esthetic studies reveal the mobilizing power in their contemplation and the capacity to bring out personal stories with healing potential. The general objective of this paper is to design and validate the PROJECTA instrument, consisting of the therapeutic use of artistic images to approach trauma or difficult conditions in therapy, by means of the association between art images and emotions, feelings or states of mind related with a traumatic experience. A mixed approach of investigation with a concurrent triangulation design has been used for the integration of qualitative and quantitative results, where qualitative research outweighs quantitative, but both have been QUAL → quan sequentially developed. The study was carried out in two phases. The first was a systematic review of the literature. The second, divided into five steps, consisted of the validation of artworks and the associated emotions with the participation of students, experts in art therapy, psychologists and educators through focus groups, interviews and an online questionnaire. The analysis techniques were qualitative and quantitative. A set of 220 artistic images linked to emotional states were proposed by experts in education, psychology and art therapy, and validated through an online questionnaire. The respondents included 228 students and professionals and for 64.55% of these images a consensus of over 80% was obtained. These images and their associated emotions were again reviewed by a confirmatory focus group. Finally, 92 artistic works were linked to primary, secondary and tertiary emotions such as love, joy, victory, surprise, balance, sense of humor, anger, sadness, fear and emptiness. In addition, there are mobilizing images that have not been related to any emotion because of the polysemy of their meanings. It concludes that PROJECTA is a visual art therapy tool that provides professionals with a resource that helps facilitate the identification, expression or demonstration of emotions or feelings related with trauma, and in challenging situations of vulnerability, psychological discomfort or post-traumatic stress.